(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The massive growth of technology in medical industry created a strong way for analyzing various diseases in the early stages. Diabetic retinopathy is a kind of common disease occur due to prolonged diabetics and their impacts are highly affects the patient health. Diabetes is the chronic disease which slowly damages the organs of the body. Retinal diseases are common with diabetic patients. Diabetic retinopathy is based on chronic diabetic that leads to mellitus. The early detection of diabetic retinopathy is important by considering various feasible parameters collected clinically and through screening images such as Optical coherence tomography (OCT) fundus images, pathology reports etc. The presented study discuss various methodology adopted for early detection of diabetic retinopathy (DR).